Sauvignon secret a wine country mystery - Crosby, Ellen (Thorndike, Me. : Center Point Pub., 2011)
When Lucie Montgomery finds the body of prominent wine merchant Paul Noble hanging from a beam in his art studio near her Virginia vineyard, she is unwittingly dragged into Noble's murky past. Once a member of the secret "Mandrake Society," Noble might have aided in a cover-up of the deaths of a disabled man and a beautiful young biochemist involved in classified government research forty years ago. A seemingly innocent favor for an old friend of her French grandfather sends Lucie to California where she teams up with ex-flame Quinn Santori. Soon the pair are embroiled in a deadly cat-and-mouse game that takes them from glittering San Francisco to the legendary vineyards of Napa and Sonoma, and back home to Virginia as they try to discover whether a killer may be seeking vengeance for the long-ago deaths. As Lucie and Quinn struggle to uncover the mystery, they must also decide whether or not they have a future together.
100105
Keywords: Montgomery, Lucie (Fictitious character); Vintners -- Virginia; Cold cases (Criminal investigation) -- California; Vineyards -- California; Large type books; Mystery fiction